Identification of Mercury in Tembang Fish (Sardinella gibbosa) and Shellfish (Marcia hiantina) in Losari Coastal Beach, Makassar - Erlani, Erlani; Mulyadi, Mulyadi; Irwansyah, Irwansyah (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Mercury was one of heavy metals that became pollutant. High level of mercury in aquatic environment could cause adverse effects on living organisms in that environment, even endanger human health in using the water and consuming the organism. This reasearch was a descriptive survey that was supported by laboratory test result in order to know mercury (Hg) level in Tembang fish (Sardinella gibbosa) and Shellfish (Marcia hiantina) in Losari coastal beach, Makassar. The result of mercury examination at Center Health Laboratory Makasar was obtained that mercury levels in Tembang Fish were 0.0150 mg/kg, 0.0133 mg/kg and 0.0126 mg/kg. Thus, the average of mercury level in Tembang fish was 0.0409 mg/kg. Meanwhile, based on examination results of mercury level in Shellfish at Center Health Laboratory, Makasar, were obtained 0.0228 mg/kg, 0.0266 mg/kg, and 0.1105 mg/kg. Thus, the average of mercury level in Shellfish was 0.1599 mg/kg. Moreover, mercury level in either Tembang fish or Shellfish in ââLosari coastal beach Makassar had fulfilled the requirement based on SNI 7387/2009 regarding Maximum Limit of Heavy Metal of Mercury.